2020
DOI: 10.1177/0735633120973432
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development of Code and Robotics Teachers Through Small Private Online Course (SPOC): Teacher Centrality and Pedagogical Strategies for Developing Computational Thinking of Students

Abstract: This study explored (1) pedagogical strategies in Educational Coding and Robotics (ECR) learning which can develop computational thinking of students and (2) the degree of teacher centrality in the ECR classroom. In addition, we investigated (3) the added value of the Small Private Online Course (SPOC) to teacher professional development (TPD). We analyzed reflections of 80 in-service teachers on TPD through the SPOC (1,091 statements) and conducted semi-structured interviews with 13 of them one year after com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In the context of visual programming, previous studies claimed that constructivism is a proper approach for teaching and learning (Bakar et al, 2019;Hadad et al, 2020). However, research findings that followed the process of creating games using the Scratch environment (Ke, 2014) found that most of the educational digital games created by students under the guidance of computer science teachers in schools were instructive in nature and may have reflected the pedagogical perspective of the teachers.…”
Section: Visual Programming -Scratch Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of visual programming, previous studies claimed that constructivism is a proper approach for teaching and learning (Bakar et al, 2019;Hadad et al, 2020). However, research findings that followed the process of creating games using the Scratch environment (Ke, 2014) found that most of the educational digital games created by students under the guidance of computer science teachers in schools were instructive in nature and may have reflected the pedagogical perspective of the teachers.…”
Section: Visual Programming -Scratch Environmentmentioning
confidence: 99%
“…In addition, it can promote interdisciplinary learning when programming artifacts is related to the curriculum in math, language, history, geography, etc. (Hadad et al, 2020). This promise is seldom realized, as a literature review conducted by Hsu et al (2018) found that most of the studies focused on programming skills training and mathematical computing, while only a few were interdisciplinary.…”
Section: Visual Programming -Scratch Environmentmentioning
confidence: 99%
“…Studies have shown that students' autonomous learning can improve learning performance and promote the cultivation of lifelong learning skills Xie & Yang, 2020). Teachers perceive self-regulated learning skills as a coping strategy of lifelong learners that usually is not required in the classroom (Hadad, Shamir-Inbal, Blau & Leykin, 2020;, and ERT was an opportunity to promote their development (Kong, 2020). However, the data regarding students needs to be treated with caution, since it is based on reports of teachers and was not triangulated with students' own perspectives.…”
Section: Benefits Of Teachers and Students In Emergency Remote Teachingmentioning
confidence: 99%
“…Embedded assessment is a fundamental aspect of instruction that helps students improve their work and contains special challenges and affordances when conducted in online environments (Blau & Shamir-Inbal, 2018;Kearns, 2012). Therefore, the issue of planning embedded assessment through routine and ERT should be included in teacher training in order to help teachers expand their experience in using diverse assessment methods at different stages in their pedagogical design (Hadad, Shamir-Inbal, Blau, & Leykin, 2020).…”
Section: Pedagogical Strategies For Emergency Remote Teachingmentioning
confidence: 99%
“…Such a description clearly fits anyone involved in program management and budgeting for that program. Hadad et al (2021), build on this premise and its consequences by drawing on Zviel-Girshin et al,…”
Section: Program Theory Logic Models and Lean Managementmentioning
confidence: 99%